Development of Pig Conventional Dendritic Cells From Bone Marrow Hematopoietic Cells in vitro - Li, Yanli; Puebla-Clark, Lucinda; Hernández, Jesús; Díaz, Ivan; Mateu, Enric (Frontiers in Immunology, 2020)
In recent years, porcine dendritic cells (DC) have been identified from pig tissues. However, studying the interaction of porcine DC with pathogens is still difficult due to the scarcity of DC in tissues. In the present work, the Flt3-ligand (Flt3L)-based in vitro derivation system was further characterized and compared with other cytokine derivation models using a combination of factors: stem cell factor (SCF), GM-CSF, and IL-4. The method using Flt3L alone or combined with SCF supported the development of pig bone marrow hematopoietic cells into in vivo equivalent conventional DC (cDC). The equivalent cDC1 (the minor population in the cultures) were characterized as CADM1+CD14–MHC-II+CD172a–/loCD1¬–CD163–DEC205+CD11R3loCD11R1+CD33+CD80/86+. They expressed high levels of Flt3, ZBTB46, XCR1 and IRF8 mRNA, were efficient in endocytosing dextran and in proliferating allogenic CD4+CD8+ T-cells, but deficient in phagocyting inactivated S. aureus. Also, after poly I:C stimulation, they predominantly produced IL-12p40a, and matured as indicated by the increase of MHC-I, MHC-II, and CD80/86. The equivalent cDC2 (the main population) were CADM1+CD14–MHC-II+CD172a+CD1+CD163–/loDEC205loCD11R3+CD11R1+CD33+CD80/86+, meanwhile, overexpressed FcεR1α and IRF4 mRNA. They showed high efficiency in the endocytosis of dextran, whereas weak in phagocytosing bacteria. They supported allogenic CD4+CD8–/CD4+CD8+ T-cell proliferation and were high producers of IL-12p40 (upon TLR7 stimulation) and IL-10 (upon TLR3/7 stimulation). TLR-ligand stimulation also induced their maturation. In addition, a CD14+ population was identified with the phenotype CADM1+CD14+MHC-II+CD172a+CD1+CD163+DEC205–CD11R3+CD11R1+CD33–/loCD80/86+. They shared some functional similarities with cDC2 and were distinguishable from macrophages. This CD14+ population was efficient in phagocyting S. aureus but showed less maturation upon TLR-ligand stimulation than cDC1 or cDC2. The alternative methods of DC derivation including GM-CSF and/or IL-4 produced mostly CADM1– cells that did not fulfill the canonical phenotype of bona fide porcine DC. Our study provides an exhaustive characterization of Flt3L-derived DC with different methods that can help the in vitro study of the interaction of DC with porcine relevant pathogens.